PENYAJIAN LAPORAN KEUANGAN PANTI ASUHAN UMMI IKHLAS KOTA JAMBI BERDASARKAN INTERPRETASI STANDAR AKUNTANSI KEUANGAN (ISAK) NO.35 - Annastasya Annastasya; Faturahman Faturahman; Puteri Anggi Lubis (CV. Aksara Global Akademia, 2023)
This research aims to present financial reports at the Ummi Ikhlas Orphanage in Jambi City based on ISAK No.35. The type of research used in this research is descriptive qualitative research. The data collection technique used was by conducting observations at the Ummi Ikhlas Orphanage, as well as conducting interviews with Mr. Ibnu Hazar Lubis, Secretary and Treasurer of the Ummi Ikhlas Orphanage. also from various written sources or existing documents provided to informants in the form of photo files of researchers at the Ummi Ikhlas Orphanage. interviews, this research uses documents related to the preparation of financial reports. This research proves that the form of financial reports at the Ummi Ikhlas Orphanage in Jambi City in 2022 has been adjusted to ISAK 35, namely consisting of a Comprehensive Income Report, Cash Flow Report, Net Asset Change Report, Financial Position Report and Notes to Financial Reports.